Vembanad Lake and Tourism (EQUATIONS, 2007)
This paper covers the impacts that tourism has had on the Vembanad Lake, the communities living around it and the impact on their livelihood. Vembanad Lake covers an area of 200 km2 and is the largest lake in Kerala. Alappuzha, Kottayam, and Ernakulam districts border it. The development of tourism in Vembanad Lake could be attributed to the Nehru Trophy Boat Race held on the Punnamda Lake, near Alappuzha every year. Now the lake attracts more than a hundred thousand tourists a year. This increase in tourism contributed to a temporary rise in employment and contributes to short-term contractual labour, but overall the sector employs a marginal percentage of local workforce. The development of the tourism industry has reduced land holdings of the communities, destroyed the ecosystem and dependent livelihoods, and there is reported trafficking of women. The development of tourism also undermines local government authority and decision-making.